Pattern of Medication Adherence, Spirituality and Viral Load amongst Adult Patients on Highly Active Antiretroviral Therapy in Rural Southwest Nigeria - Moronkeji Temitope Olanrewaju; Olatutu Ololade Olanrewaju; Azeez Oyemomi Ibrahim; Tope Michael Ipinnimo; Paul Oladapo Ajayi; Oluwafunmilayo Kehinde Sito (Nigerian Postgraduate Medical Journal)
Introduction: Previous studies have been conducted on medication adherence in Southwest Nigeria, but none of these has reported the relationship between highly active antiretroviral therapy (HAART) adherence, spirituality and viral load (VL) amongst people living with Human immunodeficiency virus (HIV)/AIDS, especially in rural settings of Southwestern Nigeria. This study assessed the pattern of medication adherence, spirituality and VL and ascertained the association of socio-demographics and spirituality on medication adherence amongst patients on HAART in rural Southwestern Nigeria. Materials and Methods: A hospital-based cross-sectional study involving 321 consented patients on HAART who were recruited by systematic sampling technique at the adult HIV clinic. Data were collected using an interviewer-administered questionnaire that assessed participants’ socio-demographic profiles, medication adherence and spirituality. Their blood samples were collected and their VLs were determined. The data were analysed using SPSS version 20. Logistic regression was done to identify the independent predictors of medication adherence. Results: The majority of the respondents reported a medium level of medication adherence (66.4%), a high level of spirituality (68.8%) and a low level of VL (67.3%). Amongst variables that had a statistically significant association with medication adherence were being educated, married, divorced, separated or widowed (P < 0.05). Furthermore, persons with high spirituality were 2.6 times more likely to be adherent to antiretroviral drugs when compared to persons with low spirituality (P < 0.05). Conclusion: It was shown that high spirituality is a positive predictor of medication adherence amongst patients on HAART. It, therefore, suggests that efforts deployed to improve the spirituality of these patients would most likely improve their medication adherence.